The clinical characteristics and prognostic value of IGFBP6 in glioma. (1st February 2022) - Zong, Zhitao; Xin, Li; Tang, Xueping; Guo, Hua
ABSTRACT: Background: Glioma is the most common intrinsic tumor in central nervous system and is characterized by their diffuse infiltration of the brain tissue. Insulin-like Growth Factor Binding Protein-6 (IGFBP6) was associated with the insulin-like growth factor binding and insulin-like growth factor II binding processes in many cancers. Herein, we aimed to investigate the biological functions and clinical features of IGFBP6 in gliomas. Methods: Totally, we collected 325 RNA sequencing data from CGGA dataset as training cohort, and 969 RNA sequencing data from TCGA dataset as validation cohort. The clinical and molecular characteristics analysis and gene ontology analysis of IGFBP6 were performed. All analyses and graphs were produced based on R language. Results: We found that IGFBP6 expression was significantly upregulated in GBM patients and downregulated in IDH mutant patients. Receiver Operating Characteristic (ROC) analysis revealed that IGFBP6 could be used as a biomarker to predict TCGA mesenchymal subtype. GO analysis revealed that IGFBP6 was correlated with immunological functions and inflammation activities. Meanwhile, higher expression of IGFBP6 suggested significant relationship with worse prognosis in glioma patients. Conclusions: Our findings improved the understanding of IGFBP6 in glioma, and IGFBP6 might be a potential therapeutic target for glioma patients in future clinical trials.